Numerical study of corrugated metal panels subjected to windborne debris impacts - Chen, W.; Hao, Hong; Du, H. (Trans Tech Publications Ltd, 2015)
Hurricane, typhoon and cyclone take place more and more often around the world with changing climate. Such nature disasters cause tremendous economic loss and casualty. Various kinds of windborne debris such as compact-Like, plate-Like and rod-Like objects driven by hurricane usually imposes localized impact loading on the structure envelopes such as cladding, wall or roof, etc. The dominant opening in the envelope might cause serious damage to the structures, even collapse. To withstand the impact of such extreme event, the requirements on panel capacity to resist windborne debris impact has been presented in the Australian Wind Loading Code (2011) [1]. Corrugated metal panels are widely used as building envelop. In a previous study, laboratory tests have been carried out to investigate the performance of corrugated metal panels subjected to a 4kg wooden projectile by considering various impact locations, impact velocities and boundary conditions. In this study, numerical models were developed to simulate the responses of the corrugated metal panels subjected to wooden debris impacts by using commercial software LS-DYNA. The predicted data from the numerical simulations were compared with the experimental results. The validated numerical model can be used to conduct intensive numerical simulation to study the failure probabilities of corrugated structural panels subjected to windborne debris impacts.